2011
DOI: 10.1074/jbc.m111.278408
|View full text |Cite
|
Sign up to set email alerts
|

COMMD1 (Copper Metabolism MURR1 Domain-containing Protein 1) Regulates Cullin RING Ligases by Preventing CAND1 (Cullin-associated Nedd8-dissociated Protein 1) Binding

Abstract: Cullin RING ligases (CRLs), the most prolific class of ubiquitin ligase enzymes, are multimeric complexes that regulate a wide range of cellular processes. CRL activity is regulated by CAND1 (Cullin-associated Nedd8-dissociated protein 1), an inhibitor that promotes the dissociation of substrate receptor components from the CRL. We demonstrate here that COMMD1 (copper metabolism MURR1 domain-containing 1), a factor previously found to promote ubiquitination of various substrates, regulates CRL activation by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…Moreover, precipitation of endogenous CCDC22 led to the recovery of endogenous Cul1, Cul2, and Cul3 ( Figure 6C). Finally, CCDC22 was able to interact with other Cullin family members (Supplemental Figure 9A), in line with similar observations for COMMD family members (16). Together, these data demonstrated that CCDC22 interacts with the ligase that targets IκB proteins for degradation and is required for its ability to ubiquitinate this substrate in vivo.…”
Section: Figuresupporting
confidence: 72%
See 4 more Smart Citations
“…Moreover, precipitation of endogenous CCDC22 led to the recovery of endogenous Cul1, Cul2, and Cul3 ( Figure 6C). Finally, CCDC22 was able to interact with other Cullin family members (Supplemental Figure 9A), in line with similar observations for COMMD family members (16). Together, these data demonstrated that CCDC22 interacts with the ligase that targets IκB proteins for degradation and is required for its ability to ubiquitinate this substrate in vivo.…”
Section: Figuresupporting
confidence: 72%
“…We postulate that the specific composition of COMMD proteins present in any given CCDC22-COMMD complex, as well as the specific CRLs to which they bind, ultimately determine their unique functions. In addition, we speculate that CCDC22 and COMMD proteins work in concert to regulate these ligases, probably acting as a complex to displace the CRL inhibitor CAND1, as recently reported in the case of COMMD1 (16).…”
Section: Figurementioning
confidence: 83%
See 3 more Smart Citations